INVESTMENT MODEL DISPLAY MATERIAL AND TECHNICAL BASE AGRICULTURAL ENTERPRISES - Tihomirova, I. V. (The actual problems of regional economy development, 2016)
For efficient production and economic activity of agricultural enterprises in modern conditions is particularly relevant issue involvement, mobilization and effective use of investment. For farms became particularly acute problem of selection and sourcing investments. It is investigated economic problems of investments forming and it’s distribution to realize an enterprise technical reequipment conventioned to alternativity of investment objects. A version of the model logistic support agricultural organizations. JEL: M 20